STUDENTS’ ANXIETY IN SPEAKING ENGLISH AT EIGHTH GRADE STUDENTS OF SMP NEGERI 3 DHARMA CARAKA TELUKDALAM - Laia, Indri Farmida (Research on English Language Education, 2022)
This research aimed at analyzing the students’ anxiety in speaking English. This research was designed in qualitative research with descriptive approach. The data of this research was gathered through observation, and interview. The procedures used during analyzing the data were reading/memoing, describing, classifying. The result of this research showed that the anxiety experienced by eighth grade students of SMP Negeri 3 Dharma Caraka Telukdalam were communication apprehension, test anxiety and fear of negative evaluation. The students’ anxieties were caused by four internal factors and five external factor. The internal factors were lack of confidence, shyness, lacks of motivation and fear of making mistake. The external factors were lack of preparation, limited vocabulary, grammatical error, friends/ classmate and embarrassment. Therefore, it can be concluded that anxiety and factors caused it influenced students’ ability in speaking English. It is suggested to English teacher to apply interesting methods to teach English speaking skill for students to avoid students’ anxiety in speaking English, and the teacher should create comfortable speaking class situation so that students can follow the speaking learning process.